2020
DOI: 10.1002/ange.201915217
|View full text |Cite
|
Sign up to set email alerts
|

Highly Crystalline and Semiconducting Imine‐Based Two‐Dimensional Polymers Enabled by Interfacial Synthesis

Abstract: Single‐layer and multi‐layer 2D polyimine films have been achieved through interfacial synthesis methods. However, it remains a great challenge to achieve the maximum degree of crystallinity in the 2D polyimines, which largely limits the long‐range transport properties. Here we employ a surfactant‐monolayer‐assisted interfacial synthesis (SMAIS) method for the successful preparation of porphyrin and triazine containing polyimine‐based 2D polymer (PI‐2DP) films with square and hexagonal lattices, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…UV–Vis spectra (black curve) revealed obvious absorbance of COF-366 film and demonstrated the characteristic Soret (S) band at 471 nm and Q band at 702 nm, which corresponded to porphyrin units. The S-band of COF-366 film was red-shifted by 24 nm compared with TAPP (red curve), which confirmed the existence of extended conjugation in COF-366 film [ 20 ].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…UV–Vis spectra (black curve) revealed obvious absorbance of COF-366 film and demonstrated the characteristic Soret (S) band at 471 nm and Q band at 702 nm, which corresponded to porphyrin units. The S-band of COF-366 film was red-shifted by 24 nm compared with TAPP (red curve), which confirmed the existence of extended conjugation in COF-366 film [ 20 ].…”
Section: Resultsmentioning
confidence: 78%
“…Burke and co-workers [ 19 ] demonstrated that acid-mediated exfoliation reactivated the imine bond exchange, which caused the COF particles to partially decompose and subsequently repolymerize during film formation, and the resulting film was highly crystalline. Sahabudeen and co-workers [ 20 ] synthesized highly crystalline films with the assistance of small molecular surfactants. In addition, template-assisted interfacial synthesis of COF films has been proven to be a feasible method to improve film crystallinity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing improvements in the bottom-up synthesis of single/few-layer COFs with increasingly large crystalline domains will also assist the experimental realisation of our proposal 57 . The relatively low tensile strengths of our considered 2D-CORF materials also permit large elastic strains with experimentally accessible applied in-plane stresses, which is essential to ensure electronic control in real-world applications.…”
Section: Discussionmentioning
confidence: 93%
“…The photoconductive properties of P5 were studied using time-resolved terahertz spectroscopy, and a thin film of P5 with a thickness of 20 nm demonstrated a p-type semiconducting behaviour with a bandgap of 1.38 eV and a hole mobility of 0.01 cm 2 V À1 s À1 . 57 The impressively large-size singlecrystalline domain makes this method a promising pathway to monolayer 2DSP.…”
Section: Polymerization On a Air/liquid Interfacementioning
confidence: 99%